PENGEMBANGAN MEDIA DIGITAL EDUCAPLAY TEMA HOBBYS UNTUK KETERAMPILAN MEMBACA BAHASA JERMAN KELAS XI SMA - Bataona, Genoveva; Wahyuningsih, Fahmi (LATERNE, 2025)
This study aimed to develop digital learning media based on Educaplay with the theme Hobbys to reading skills in German language learning for grade XI high school students. The research was motivated by the challenges students faced in understanding German texts and the limited use of interactive media in the learning process. The method used was Research and Development (R&D) with the Borg and Gall model (1989), limited to the design revision stage. The developed media utilized four main features of Educaplay namely Slideshow, Froggy Jumps, Fill in the Blanks, and Matching Pairs. The validation results showed a feasibility level of 82% from material experts (feasible) and 98% from media experts (very feasible). Therefore, the media was declared feasible to be used as an interactive learning media for German reading skills of grade XI high school students.